2020
DOI: 10.3748/wjg.v26.i26.3767
|View full text |Cite
|
Sign up to set email alerts
|

SpyGlass application for duodenoscope working channel inspection: Impact on the microbiological surveillance

Abstract: BACKGROUND Patient-ready duodenoscopes were designed with an assumed contamination rate of less than 0.4%; however, it has been reported that 5.4% of clinically used duodenoscopes remain contaminated with viable high-concern organisms despite following the manufacturer’s instructions. Visual inspection of working channels has been proposed as a quality control measure for endoscope reprocessing. There are few studies related to this issue. AIM To investigate the types, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…SpyScope (SpyGlass™ DS Direct Visualization System, Boston Scientific Corp, MA, USA) was used for 27 the visual inspection of the residual fluid inside working channel (Fig. 1a,b).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…SpyScope (SpyGlass™ DS Direct Visualization System, Boston Scientific Corp, MA, USA) was used for 27 the visual inspection of the residual fluid inside working channel (Fig. 1a,b).…”
Section: Methodsmentioning
confidence: 99%
“…Corp, MA, USA) was used for 27 the visual inspection of the residual fluid inside working channel (Fig. 1a,b).…”
Section: Protocol For Cleaning Simethiconementioning
confidence: 99%
See 1 more Smart Citation
“…Visual inspection using a borescope has been suggested as a quality assurance step in reprocessing to detect scratches and other irregularities within endoscope channels. Several studies identified internal defects of instrument channels to be more frequent than anticipated, increasing their microbiological contamination susceptibility [6,10,11]. Inconsistencies in recommended quality measures to detect microbiological debris in endoscope channels may also pose safety risks.…”
Section: Introductionmentioning
confidence: 99%
“…13 Studies that used borescopes have identified visible defects in nearly 100% of previously uninspected endoscopes, including residual soil, debris, retained fluid, and damage. 12,[14][15][16][17][18][19][20] In some cases, new scratches and channel shredding appeared within a few uses 16,20 and critical defects requiring repair were observed. 16,18,19 Given that researchers have also detected soil and microbial bioburden on more than 50% of fully-processed endoscopes, [17][18][19]21 there is a clear need to improve visual inspection practices to ensure that endoscopes are free of visible damage and soil before each procedure.…”
mentioning
confidence: 99%